The Wolf From Dmanisi and Augmented Reality: Review, Implications, and Opportunities - Bartolini Lucenti, Saverio; Bukhsianidze, Maia; Martínez-Navarro, Bienvenido; Lordkipanidze, David (Frontiers in Earth Science, 2020)
In the complex scenario of Plio-Pleistocene mammalian faunal-turnovers, recent research on canids has revealed an increasingly higher number of species than previously thought. In this framework, Georgia had a key role in the biogeographic dispersion of fauna from/to Asia, Africa, and Europe. Historically attributed to C. etruscus, the rich Canis material recovered from Dmanisi possesses certain peculiar cranial and dentognathic features, which cannot be regarded only as intraspecific variability. We revealed closer similarities between the Dmanisi wolf and the younger European Canis mosbachensis, rather than with other Early Pleistocene canids as C. etruscus and C. arnensis. The discovery of a Canis borjgali sp. nov. in Dmanisi, with characteristics close to those of C. mosbachensis, changes radically the idea of C. lupus evolution as it is conveyed today, invalidating the paradigm C. etruscus-C. mosbachensis-C. lupus lineage. Furthermore, the geographic position of Dmanisi in the Caucasian area offers interesting insights regarding the Asian canids and their dispersion into Europe and Africa, an aspect still poorly investigated. The exquisite state of preservation of the fossil from Dmanisi combined with novel 3D visualization and a digital imaging techniques gives us the opportunity to increase the outreach of the research thanks to user-friendly and free tools. Here, for the first time, we employed augmented reality on a few specimens of Canis borjgali sp. nov. through a simple web-app. The extraordinary chance offered by these technologies has yet to be implemented in scientific research and dissemination, particularly in paleontology.